2020
DOI: 10.3390/ijms21155279
|View full text |Cite
|
Sign up to set email alerts
|

Sickle Cell Disease: A Paradigm for Venous Thrombosis Pathophysiology

Abstract: Venous thromboembolism (VTE) is an important cause of vascular morbidity and mortality. Many risk factors have been identified for venous thrombosis that lead to alterations in blood flow, activate the vascular endothelium, and increase the propensity for blood coagulation. However, the precise molecular and cellular mechanisms that cause blood clots in the venous vasculature have not been fully elucidated. Patients with sickle cell disease (SCD) demonstrate all the risk factors for venous stasis, activated en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 133 publications
(184 reference statements)
0
24
0
1
Order By: Relevance
“…The vascular damage induced by ROS is worsened by NO reaction with superoxide, that forms peroxynitrite, a highly harmful molecule for the endothelium [ 49 ]. The resulting inflammation and hypoxia further increase tissue factor expression and the consequent activation of the coagulation cascade [ 50 ]. One of the principal consequences of this inflammatory activation caused by free heme is the release of neutrophil extracellular traps (NETs), mesh-works of chromatin fibers released by neutrophils, which favor coagulation by serving as a scaffold for the activation of platelets and coagulation factors [ 51 ].…”
Section: Pathophysiology Of Thrombosis In Immune Mediated Hemolysismentioning
confidence: 99%
“…The vascular damage induced by ROS is worsened by NO reaction with superoxide, that forms peroxynitrite, a highly harmful molecule for the endothelium [ 49 ]. The resulting inflammation and hypoxia further increase tissue factor expression and the consequent activation of the coagulation cascade [ 50 ]. One of the principal consequences of this inflammatory activation caused by free heme is the release of neutrophil extracellular traps (NETs), mesh-works of chromatin fibers released by neutrophils, which favor coagulation by serving as a scaffold for the activation of platelets and coagulation factors [ 51 ].…”
Section: Pathophysiology Of Thrombosis In Immune Mediated Hemolysismentioning
confidence: 99%
“…Virchow’s triad of hypercoagulability, endothelial dysfunction, and stasis, the underlying pathophysiology of venous thrombosis, is usually present in SCD patients, leading to an increased risk of thromboembolic events [ 5 ]. The average age at which venous thrombosis is diagnosed in the general population is 65 years, while the average age for high-risk thrombophilia is 30 years, which is comparable to the average age at which venous thrombosis of SCD is diagnosed [ 4 ]. A cross-sectional study of 404 patients at the Johns Hopkins Sickle Cell Center reported a median age of venous thrombosis diagnosis in SCD of 29.9 years, with 25% of the study population reporting a history of venous thrombosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased risk of venous thrombosis and pulmonary embolism in SCD patients with associated significant mortality [ 4 ]. A high index of suspicion is important for early diagnosis, and prompt intervention is warranted for optimal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…RBCs expressing the HOD antigen, transfused into animals with SCD (Hgb SS), did not result in an increase in responsiveness or in the magnitude of responsiveness compared with those transfused into animals with Hgb AS or Hgb AA ( 67 ). Murine models of SCD, summarized by Lizarralde-Iragorri and Shet ( 68 ), are just that; as such, it is not entirely clear how to interpret these data in the context of human SCD.…”
Section: Inflammation and Rbc Alloantibody Induction In Murine Modelsmentioning
confidence: 99%